Length-weight and length-length relationship among the body parts of batak fish (Tor soro) from the upstream of the Aek Godang River, North Sumatera Province - Elvi S Sinaga; Chaidir P Pulungan; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Tor soro is a North Sumatran endemic species. This fish have high economic value and play important role in Batak’s culture. Biological information on this fish, including the morphological characteristic, however, is rare. To understand the information on length-weight relationship, a study has been conducted from March to June 2015. The fish was sampled from the Aek Godang River, especially in the Banuaji (St 1) and the Dolok Nauli (St 2) villages. Totally 123 fish were captured. Several body parts such as total length, head length, fork length, caudal rod length, body height and body weight were measured and then compared to standard length in order to understand the growth pattern of the fish. Results shown that the length-weight relationship of male and female was isometric (male b=3.039 and female b=3.024). The coefficient correlation (r) values of the relationship between standard length and other body parts ranged from 0.812-0.994. It’s indicate that there is very significant relationship between standard length and the length of other body parts.Keyword: Tor soro, lenght-weight relationship, Aek Godang River, North Sumatera Province